SISTEM KOMPENSASI GURU HONORER MELALUI KANTIN SEHAT DI MADRASAH IBTIDAIYAH NEGERI 3 LAMPUNG SELATAN - Selvia Rani Rahayu; Idiyawati; Sahrizal; Nurul Hidayati Murtafiah (UNISAN JURNAL, 2022)
This study aims to photograph the compensation system for honorary teachers at an Islamic Elementary School 3, South Lampung. By adopting a qualitative approach, data was collected through the distribution of questionnaires aimed at exploring the perceptions of honorary teachers with regard to the compensation system implemented in their place of work. compensation system by honorary teachers. The overall compensation system applied to honorary teachers has not met the expectations of honorary teachers. Based on research from the Department of National Education's services development center, there are around 640 elementary schools that already have canteens. However, there are still around 60% of schools in Lampung province that already have canteens but do not meet health requirements. Therefore, improving the honorary teacher compensation system through managing healthy canteens and providing sales facilities in the canteen so that the compensation received is sufficient to support teacher effectiveness and productivity in teaching.